2024
DOI: 10.1038/s41598-023-50735-8
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for transesophageal echocardiography view classification

Kirsten R. Steffner,
Matthew Christensen,
George Gill
et al.

Abstract: Transesophageal echocardiography (TEE) imaging is a vital tool used in the evaluation of complex cardiac pathology and the management of cardiac surgery patients. A key limitation to the application of deep learning strategies to intraoperative and intraprocedural TEE data is the complexity and unstructured nature of these images. In the present study, we developed a deep learning-based, multi-category TEE view classification model that can be used to add structure to intraoperative and intraprocedural TEE ima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Steffner K. et al pioneered the AI-based interpretation of TEE images by developing a convolutional neural network (CNN) to accurately identify standardized TEE views. This demonstration of effective AI classification opens the door to advanced deep learning analyses in intraoperative and intraprocedural TEE imaging [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Steffner K. et al pioneered the AI-based interpretation of TEE images by developing a convolutional neural network (CNN) to accurately identify standardized TEE views. This demonstration of effective AI classification opens the door to advanced deep learning analyses in intraoperative and intraprocedural TEE imaging [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…AI is also being developed for transesophageal echocardiography (TEE). Steffner et al showed that AI could accurately be used to classify TEE views [55]. Yu and colleagues developed an algorithm for TEE to automatically calculate the mitral annular plane systolic excursion (MAPSE) which allows the evaluation of LV function.…”
Section: Discussionmentioning
confidence: 99%